FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP MUSCULOSCELETAL DISORDERS PADA PERAWAT DI RUMAH SAKIT UMUM SARI MUTIARA MEDAN TAHUN 2017 - Taufik, Rizki; Ketaren, Otniel; Salmah, M. Sidan Umi (Jurnal Riset Hesti Medan, 2018)
AbstractMusculosceletal complaints are a complaint on the skeletal muscle sections felt by a person starting from a very mild to very painful complaint. If the muscles receive static loads repeatedly and over a long period of time, they can cause complaints of joints, ligaments and tendons. Skeletal muscle complaints generally occur due to excessive muscle contraction due to heavy workload with long duration of loading.The purpose of this study was to analyze the factors that influence musculosceletal disorders in nurses. This research is an analytic survey research with cross-sectional approach. The study was conducted at Sari Mutiara General Hospital Medan in ICU room and IGD room. The sample size is 38 people. Data analysis was done univariat, bivariate using chi-square, and multivariate test using multiple logistic regression test.Based on the result of the research showed that the factors influencing musculoskeletal disorders at the nurses in public hospital of pearl extract are gender (p-value = 0,002), work period (p-value = 0,049), and work attitude (p-value = 0,000). While the unrelated variable is age ((p-value = 0.147) .The attitude of work is the biggest variable of influence on musculoscelet disorders with (p-value = 0,003; OR = 17,627; 95% CI 2,68-115,957) work has a 17.627 times greater risk of complaints of musculosceletal disorders.It is expected that the nurse should continue to pay attention to the movement pattern when doing the activity, so that there is no wrong working attitude, so it can trigger the emergence of musculoscelet disorders.Key words: Factors, musculosceletal disorders